Ionospheric disturbances before and after the january 14, 2018 earthquake in Peru - Sotomayor Beltran, Carlos (2019)
An earthquake of Mw 7.1 occurred on January 14, 2018 in the southern coast of Peru. In this study, public available Global Ionospheric Maps (GIMs) provided by the Center for Orbit Determination in Europe (CODE) were used to look for ionospheric disturbances pre- and postearthquake. Twelve days before the seismic event, a positive anomaly was detected at low latitudes in the northern hemisphere in differential vertical total electron content maps. Moreover, given the low-latitude nature of this incident, changes in the shape of the Equatorial Ionization Anomaly (EIA) were analyzed as well. A significant amplification of the northern crest in the EIA of 33.3 % was also observed 12 days before the earthquake. Because the geomagnetic and solar conditions for January 2, 2018 were very quiet and also knowing that natural ground radioactivity produced by the earthquake's preparation can increase the total electron density in the EIA, it is considered that this ionospheric disturbance is product of the earthquake's preparation. Additionally, the detection of a negative ionospheric anomaly 2 days after the incident is reported. An association to the earthquake of this negative disturbance is hinted at, due to the also the rather quiet geomagnetic and solar conditions after the seismic occurrence.